Rorty and Lyotard, or about conversation and tragedy - Kwiek, Marek (My University, 1996)
There are many more and less important points of discord between Richard Rorty and Jean-Francois Lyotard, there are many differences of fundamental importance for the two philosophers. (Lyotard speaks precisely of a "radical divergence" between them. One could write a lot about their different attitude towards utopia, liberal democracy, shape, place and role of philosophy in future culture, towards painting and literature, history of philosophy, the man/his work distinction, different account of the role of particular great philosophers in recent history of philosophy (of Kant in particular) etc. etc. What we are interested here in, though, is mainly one problem and one difference revealing itself through Rortyan disagreement with the Lyotardian idea of "différends". In the statement that the task of philosophy is to "bear witness to différends" (to maintain them and to search for new idioms coined especially for the purpose of expressing them rather than turning them into mere litigations) on Lyotard’s part - and, on the other hand, in questioning of any positive role of différends in culture on Rorty’s part, there is probably the crucial difference between them. Let us say by virtue of an Introduction the following: if Lyotard says in a discussion with Rorty that "il y a entre Richard Rorty et moi un différend", then the point is undoubtedly worth being discussed. Within the "différend" between Lyotard and Rorty (which within detailed discussions in The Différend. Phrases in Dispute of the former seems to be too strong a word, the one characterized by emotions of the ongoing controversy between them), I will confine myself to tracing why Rorty does not recognize différends as such, that is to say, to just a part of a larger "différend" between them, but potentially a very important part. For it seems to me that in his inacceptance of différends there is also the pragmatic inacceptance of tragedy.
Keywords: Richard Rorty; Jean-Francois Lyotard; What Is Postmodernism?; Consequences of Pragmatism; American neopragmatism; new pragmatism; postmodernism; conversation; liberal ironist; democracy; differend; le differend